PENGARUH PEMBERIAN MASSASE PUNGGUNG TERHADAP PENURUNAN SKALA NYERI PADA PASIEN APPENDIKTOMI DI RSUD RANTAU PRAPAT - Hamonangan Damanik; Sarida Surya Manurung; Deddy Sepadha Putra Sagala (Jurnal Ilmiah Keperawatan IMELDA, 2022)
ABSTRACT Appendicitis is a condition in which inflammation occurs due to infection in the appendix or appendix. Infections in the appendix or appendix can cause acute inflammation, so immediate surgery is needed to prevent complications that can generally endanger health. This study aims to analyze the effect of giving back massage to reduce pain scale in appendectomy patients at Rantau Prapat Hospital. The type of research used is quantitative with a quasi-experimental design with a one-group pre-test/post-test design. The study was conducted in July 2021 at the Rantau Prapat Hospital. The population in this study were all post appendectomy patients who were treated in June-July 2021. The population in this study was 16 people. The sampling technique in this study was a total sampling technique, thus the number of samples in this study was 16 people. The results of data analysis carried out using the t test obtained results with a probability value (p) = 0.000 (p <0.05) meaning that there was an effect of back massage on decreasing pain levels in post-appendectomy patients. It is hoped that the hospital will always improve services to patients by developing and applying non-pharmacological therapy techniques in addition to pharmacological treatment that is effective in reducing pain scale in patients, especially postoperative patients.